Pembiayaan Pembiayaan Bank Syariah Untuk Mengembangkan UMKM: Pembiayaan Bank Syariah Untuk Mengembangkan UMKM (Studi Kasus Pada Nasabah BRI Syariah Kantor Cabang Jambi) - Afriyadi, Muhammad Muchsin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2020)
ABSTRACT Islamic financing their customers can make free of the economic difficulties faced, on the basis of sharia aspects and avoid usury, this is expected to be a way for customers of Bank Syariah can be separated from the problem of poverty faced. The research objective is to study in depth the perception of consumers about financial products and the impact of their financing by BRI Syariah Kantor Cabang Jambi to develop SMEs. Method research explain that location research on BRI Syariah Kantor Cabang Jambi and at home each subject. Approach research Qualitative with type research phenomenology, experience subjective or experience phenomenological; or something studies about awareness from perspective principal from someone. Researchers with approach phenomenologically attempted understand mean from something event and each other influence with human in situation certain. Results research showing that perception customers from Informant revealed satisfaction to financing already conducted at BRI Syariah Kantor Cabang Jambi is good from systems, rules, services or installments to be paid. Impact from existence financing from BRI Syariah Kantor Cabang Jambi against the development of SMEs is increased capital used for increase the stock of goods to be sold, added tool support effort, expand and fix the place effort, from development the benefits from business the too increased. Keywords : Financing, Islamic Banking, SMEs